The German equity trading landscape - Peter Gomber (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
This paper describes cash equity markets in Germany and their evolution against the background of technological and regulatory transformation. The development of these secondary markets in the largest economy in Europe is first briefly outlined from a historical perspective. This serves as the basis for the description of the most important trading system for German equities, the Xetra trading system of Deutsche Börse AG. Then, the most important regulatory change for European and German equity markets in the last ten years is illustrated: the introduction of the Markets in Financial Instruments Directive (MiFID) in 2007. Its implications on equity trading in Germany are analyzed against the background of the current status of competition in Europe. Recent developments in European equity markets like the emergence of dark pools and algorithmic / high frequency trading are portrayed, before an outlook on new regulations (MiFID II, MiFIR) that will likely come into force in early 2018 will close the paper.
urn:nbn:de:hebis:30:3-395922
Keywords: 330; MiFID II; MiFIR; equity trading; electronic trading; cash equity markets